Molecular mechanisms underlying heat or tetracycline treatments for citrus HLB control. Issue 1 (1st June 2018) - Ding, Fang; Allen, Victoria; Luo, Weiqi; Zhang, Shouan; Duan, Yongping
Abstract: Huanglongbing (HLB), a destructive plant bacterial disease, severely impedes worldwide citrus production. In our previous reports, we revealed the molecular mechanisms of host plant responses that underlie thermotherapy against HLB. In this study, we investigated the molecular mechanism underlying heat or tetracycline treatments on the HLB bacterium, ' Candidatus Liberibacter asiaticus' (Las) by focusing on Las prophage/phage conversion under stress conditions. By comparing the prophage FP1 and FP2 copy number to the copy number of 16S rDNA in HLB-affected plants, we found that the relative copy number of both FP1 and FP2 increased significantly, ranging from 3.4- to 6.7-fold change when Las-infected samples underwent a temperature shift from 23 to 37, 42 or 45 °C. When treated with tetracycline at 50–150 and 200–250 µg/ml, respectively, the relative copy number of both FP1 and FP2 increased by 3.4- to 6.0-fold. In addition, analyses of Las prophage structural gene and antirepressor gene copy numbers showed similar trends for all treatments. Furthermore, transmission electron microscopy provided direct evidence of lysogenic to lytic conversion upon temperature increase. These results not only provide new insight into the molecular mechanisms underlying heat or tetracycline treatment but also suggest a novel HLB control strategy by enhancing the endogenous conversion from Las prophages to phages. Citrus disease: Fighting one infection with another: Heat treatment to cure citrus plants of Huanglongbing (HLB) works not by killing the HLB bacteria directly but by triggering a virus to attack them. HLB, also known as citrus greening because it causes plants to produce green, bitter fruit, threatens citrus production worldwide. No commercial-scale treatments are available, but thermotherapy, growing plants at 40 °C or higher, has recently been shown to reduce symptoms. YongPing Duan and Fang Ding at the USDA Horticultural Research Laboratory in Florida investigated how the thermotherapy works. They found that heat treatment triggered a stress response in a virus asymptomatically infecting the bacteria, causing it to multiply rapidly and killing the HLB bacteria. Heat treatment eliminated both the bacteria and HLB symptoms; application of the antibiotic tetracycline produced the same effect. These results may help in identifying potential treatments for HLB.